EKSPLORASI KREATIF MELALUI PENGINTEGRASIAN KEBHINEKAAN SENI VISUAL DALAM PEMBENTUKAN KARAKTER SISWA SMAN 1 TERARA - Vina, Irvina Astrini Arianti; Itriani, Laela Abidatul; Rahman, Diva; Diana, Diana; Hadiansyah, Lalu Muhammad; Herianto, Edy (LPPM Institut Pendidikan Nusantara Global, 2023)
This research aims to investigate how visual arts can influence students' creativity and develop more positive characters. A qualitative study combined with a case study research style was the methodology used. PPKn professors and class Data collection methods include documentation, interviews, and cross-referencing observations with information from related magazines. The inductive analysis model is used as a data analysis method in this research. Research findings show that learning media has a significant impact on the way students develop their personalities and creative thinking, teacher's creativity in choosing the right media also very important, as is the case with teachers at SMA Negeri 1 Terara who have succeeded in using learning media in the form of visual arts to create student creativity in visual art form and develop a more positive student character.